Concomitant extraction process of niobium at the titanium tetrachloride production - Sarsembekov, Т.К.; Yanko, Т.B.; Sidorenko, S.A.; Pylypenko, M.M. (Вопросы атомной науки и техники, 2020)
Development of the fundamentals of a technology for producing niobium by the concomitant extraction in the process of production of titanium tetrachloride from titanium raw materials. The paper provides data on the amount of niobium contained in the feedstock to produce titanium tetrachloride, the distribution of niobium during processing by products and waste. The forms of phase transformations and transitions of niobium during processing are considered. Schemes for processing niobium-containing chloride materials and technologies for their further application for producing alloys for nuclear power are proposed.